Implementasi Program Perpustakaan Keliling oleh Perpustakaan Soeman HS dalam Meningkatkan Minat Baca Siswa Sekolah di Kota Pekanbaru - Daffa Ahmad Iskandar; Virna Museliza; Sitti Rahmah; Candra Jon Asmara (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
The purpose is to identify the Implementation of the Mobile Library Program by the Soeman HS Library in Increasing the Reading Interest of School Children in Pekanbaru City. This research was conducted using a descriptive qualitative research approach. Research data collection was carried out through observation, interviews, and documentation. The study was conducted at the Riau Province Library and Archives Service, and the research period took place from January to March 2025. The research results indicate the existence of Standards and Targets, Resources, Inter-organizational Relations and Activity Strengthening, Characteristics of Implementing Agents, as well as Social, Economic, and Political Conditions. The organization and development of mobile libraries have the main objective of educating the nation and building character through library services that are accessible to the general public. Policy standards and recommendations, as well as the level of target achievement in increasing reading interest, can be measured using several indicators, such as: the number of readers, whether there is an increase in the number of people reading books, articles, or other reading materials. Resources to increase reading interest can include books, libraries, and literacy activities. Reading frequency refers to how often a person reads in a day, week, or month. Communication between organizations and the strengthening of activities can be carried out to create mutual understanding and maintain good relationships between organizations and their audiences.